2016
DOI: 10.1038/npjgenmed.2016.26
|View full text |Cite
|
Sign up to set email alerts
|

Clinical detection of deletion structural variants in whole-genome sequences

Abstract: Optimal management of acutely ill infants with monogenetic diseases requires rapid identification of causative haplotypes. Whole-genome sequencing (WGS) has been shown to identify pathogenic nucleotide variants in such infants. Deletion structural variants (DSVs, >50 nt) are implicated in many genetic diseases, and tools have been designed to identify DSVs using short-read WGS. Optimisation and integration of these tools into a WGS pipeline could improve diagnostic sensitivity and specificity of WGS. In additi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
31
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 61 publications
0
31
0
Order By: Relevance
“…Performance-wise, low-coverage WGS consistently showed high concordance with microarray and high-coverage WGS in our analysis. It As WGS studies become less expensive, we foresee that in the future low-coverage WGS may prove to be replacing clinical microarray testing for cancers 33 , developmental disabilities, congenital anomalies [34][35][36] , autism spectrum disorder 37 , and many other genetic diseases 29 . Citing the benefits of WGS, a recent study compared the performance of low-coverage WGS versus microarrays on rare and undiagnosed cases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Performance-wise, low-coverage WGS consistently showed high concordance with microarray and high-coverage WGS in our analysis. It As WGS studies become less expensive, we foresee that in the future low-coverage WGS may prove to be replacing clinical microarray testing for cancers 33 , developmental disabilities, congenital anomalies [34][35][36] , autism spectrum disorder 37 , and many other genetic diseases 29 . Citing the benefits of WGS, a recent study compared the performance of low-coverage WGS versus microarrays on rare and undiagnosed cases.…”
Section: Discussionmentioning
confidence: 99%
“…At 2-4x coverage, WGS provides thousands of read pairs per 100kb segment, a substantive amount enough to enable sensitive CNA detection. This provides an improved resolution compared to SNP microarrays in which there are approximately 60 probes per 100kb segment.Identifying copy number variation with high coverage WGS data have been studied extensively in basic and clinical research settings[29][30][31] . For example, in a recent systematic benchmark, Trost et al reported good performance of using >20x WGS data for identifying small-scale CNVs (1 -100kb)32 .…”
mentioning
confidence: 99%
“…Clinical WGS continues to improve with respect to rate of genetic diagnosis and time to diagnosis 27 . In particular, the diagnostic rate is increasing through ongoing identification of novel disease genes, improved reference genome sequences, and better identification of disease-causing copy number, repeat expansion, regulatory, splicing and structural variations 32, [43][44][45][46][47][48][49][50] . These recent advances were not reflected in the current study.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical detection of SVs in Mendelian diseases has been considered by e.g., Noll et al (2016) but to our knowledge no prioritisation approach for oncology is publicly available. The mechanisms for oncogenic driver generation include activating fusions combining the coding frames (quite often in the intronic regions) of two genes, as well as truncating mutations in tumor suppressor genes or whole exon losses.…”
Section: Introductionmentioning
confidence: 99%